Analisis Tindak Tutur Ilokusi dalam Wacana Pembaca Menulis pada Surat Kabar Jawa Pos Edisi September 2014 - Muwalidah, Isma Savanty, Prof. Dr. Abdul Ngalim, M.Hum (2015)
This Study has two objectives. (1) Describe who the speaker and hearer contained in the discourse readers writing in Java Pos newspaper of September edition 20114. (2) Describe the criteria speech acts in discourse writing in te Java Pos newspaper edition of September 2014. The research method using qualitative descriptive. the object of this study is to discourse readers writing in the Java Pos newspaper edition of September 2014. data collection techniqus in this study using methods refer to. data analysis techniques using techniques expand. results of the study found. 1) All the research data has speaker and hearer. (2) There are 34 research an assertive speech act, 32 the results of the research are assertive speech act complained of, first results of the study are reported assertive speech acts, and the first results of the research are informing assertive speech acts. directive speech acts are 73 research, 28 research including begging directive speech acts, 24 the results of the study suggest. Expressive illocutionary speech acts there are 12 research, 11 research results are illocutionary speech acts expressive praise.